READY FOR TAKE OFF. - HITT, JACK (Smithsonian, 2016)
The article discusses aspects of building flying cars as of March 2016. It looks at the desire of Sam Bousfield, inventor and founder of Samson Motorwork, to build a flying car which grew out of a collaboration with adventurer Steve Fossett. It discusses the efforts of engineer Chris Gerdes to solve novel problems facing autonomous driving, and the Ehang 184 concept car built by Chinese company Ehang Inc.